Keszthely ou Le château hongrois comme démonstration du savoir (Theatrum historiae, 2012)
The article deals with life style of György Festetics (1755–1819) in his country residence Keszthély at the northern coast of the Balaton around 1800. His court architect György Rantz rebuilt the castle in neo-classicist and romantic style and Festetics organized regular musical and theatrical performances there. From 1817 he arranged twice a year literary festivity called Helikon in his castle. Festetics located also a large and splendid library (1778: 8000 books – 1819 already 25000 books) there. Moreover, he founded agricultural school called Georgicon in Keszthely in 1797 and invited several economic and agricultural experts to improve incomes of his estates.
Keywords: Hungary; the Festetics; Keszthély castle; 18 century